Climate and weather services can enhance Ethiopian farmers’ resilience to climate change: Economy-wide impact analysis - Tamru, Seneshaw; Hansen, James; Zebiak, Stephen; Tesfaye, Abonesh; Minten, Bart; Demissie, Teferi; Radeny, Maren A.O.; Tesfaye, Kindie; Solomon, Dawit (Elsevier, 2025)
Weather and climate services (WCS) are particularly important in Sub-Saharan Africa, where weather-dependent agriculture is the main source of livelihood, and where erratic weather patterns and extreme weather events have major impacts on rural livelihoods and food security. However, despite their importance, their effects on the agriculture sector and the overall economy are not well understood. For the case of Ethiopia, we use a computable general equilibrium modeling approach with the latest Ethiopian social accounting matrix data to estimate the potential contribution of WCS to macroeconomic variables, including growth in gross domestic product nationally and by sector. The analysis incorporates results of a separate econometric analysis of household survey data from five major regions in Ethiopia, which showed WCS use is associated with increased agricultural productivity. We estimate that increased agricultural productivity associated with WCS contributes to overall economic growth of more than 6 %, with a likely positive effect on farmers’ resilience to climate variability and change. The positive impact of WCS on agricultural productivity propagate to the overall economy, as evidenced by the considerable positive effect on GDP especially from the more climate sensitive sectors such as agriculture.